Caught between nationalism and internationalism: replicating histories of Antarctica in Hobart. Issue 3 (15th March 2016) - Leane, Elizabeth; Winter, Tim; Salazar, Juan Francisco
Abstract: In December 2013, a replica of 'Mawson's Hut' (a historic structure in Antarctica) joined a growing list of polar tourist attractions in the Australian city of Hobart, Tasmania. Initially promoted as the city's 'latest tourist hotspot, ' the 'replica museum' quickly took its place in Hobart's newly redeveloped waterfront, reinforcing the city's identity as an 'Antarctic Gateway'. The hut forms part of a heritage cluster, an urban assemblage that weaves together the local and national, the past and present, the familiar and remote. In this article, we examine the replica hut in relation to the complex temporal and spatial relations that give it meaning, and to which it gives meaning. Our focus is the hut as a point of convergence between memory, material culture and the histories – and possible futures – of nationalism and internationalism. We argue that the replica hut, as a key site of Hobart's Antarctic heritage tourism industry, reproduces and prioritises domestic readings of exploration and colonisation over a reading of Antarctic engagement as a transnational endeavour. However, like other 'gateway city' heritage sites, it has the potential for aligning with a larger trend in international heritage conservation and heritage diplomacy, that of prioritising narratives of the past that weave together transnational connections and associations.